Onset risk factors for youth involvement in cyberbullying and cybervictimization: A longitudinal study - Sorrentino, Anna; Esposito, Alessia; Acunzo, Debora; Santamato, Margherita; Aquino, Antonio (Frontiers in Psychology, 2023)
Introduction Cyberbullying and cybervictimization are spread worldwide, and due to COVID-19, an increasing number of children and adolescents have been impacted. Since the beginning of the twenty-first century, research has investigated and highlighted the key risk factors for cyberbullying and cybervictimization, and numerous anti-cyberbullying prevention and intervention programs have been developed and assessed for their efficacy. Despite this, no studies have specifically focused on the individual, relational, and contextual risk factors associated with the onset of youth involvement in cyberbullying and cybervictimization. Methods To address this lacuna, 333 Italian students aged 10–16 years (M = 12.16, SD = 1.35) were involved in a year-long longitudinal study and filled in the anonymous online actuarial Tabby Improved Checklist two times with a 6-month interval. Onset risk factors for cyberbullying and cybervictimization have been separately analyzed by excluding all students involved in cyberbullying from the original sample or in the cybervictimization baseline (T1). Results The results showed that being male, being involved in school bullying, having low levels of awareness of online risk, and having high levels of affective empathy were all significant onset risk factors for cyberbullying. Similarly, being male, being involved in school bullying and victimization, having high levels of affective empathy, and moral disengagement were onset risk factors for cybervictimization. Conclusion Given the negative psychological and behavioral consequences of cyberbullying and cybervictimization, this article includes discussions on practical and policy implications for future research, stressing the need to develop, implement, and evaluate the effectiveness of primary prevention programs addressing and managing onset risk factors for cyberbullying and cybervictimization.